Pengaruh Terapi Bekam Kering Berbasis Elektrik terhadap Tekanan Darah pada Penderita Hipertensi di Desa Talang Kecamatan Bayat Klaten - Dewi Asih; Atik Aryani; Widiyono Widiyono (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Hypertension is a serious, incurable health condition. Patients with high blood pressure require lifelong treatment to control their blood pressure and prevent significant increases. One non-pharmacological therapy for lowering blood pressure is electric-based dry cupping therapy. To determine the effect of electric-based dry cupping therapy on blood pressure in hypertensive patients in Talang Village of Bayat District in Klaten. This study employed a pre-experimental design using a one-group pretest-posttest approach. The sample included 37 respondents selected through purposive sampling. Data collection used blood pressure measurement forms, and data analysis used a paired t-test. The researcher administered electronic cupping therapy for 15 minutes, then measured blood pressure and recorded the results on an observation sheet. The study found mean pre-test values of 157 mmHg (systolic) and 88 mmHg (diastolic), and mean post-test values of 150 mmHg (systolic) and 84 mmHg (diastolic). Bivariate analysis yielded a p-value of 0.001 (p < 0.05), indicating that electric-based dry cupping therapy lowers blood pressure in hypertensive patients. Health education using video media has an effect on patients experiencing preoperative anxiety.